TWO PHASE FLOW USING ELECTRICAL TOMOGRAPHY - Faizatul Khasanah Sugeng, Faizatul Khasanah (2010)
The aim of this project is to improve the performance of current flow rigs to enable bubble flow regime, to fabricate new sensor of ERT for data acquisition and to calculate the void fraction using the image processing techniques.